2006
DOI: 10.1002/cvde.200506463
|View full text |Cite
|
Sign up to set email alerts
|

Homoepitaxial Growth on a 4H‐SiC C‐Face Substrate

Abstract: Homoepitaxial growth on a 4H-SiC carbon face (C-face) was investigated. The C-face showed a similar site-competition phenomenon to that seen on a 4H-SiC Si-face. This site-competition phenomenon was distinctly sensitive to growth pressure. The surface morphology of the C-face epitaxial layer was sensitive to surface imperfections on the substrate. The growth window of 4°off-axis, C-face substrates was shown to be wider than that of the corresponding Si-face. A specular surface morphology without a bunched step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Homoepitaxy of dislocation-free 4H-and 6H-SiC(0001) by using small (0.4 mm × 0.4 mm) mesa structures is also reported [210]. More recently, it was found that 4H-SiC without 3C-SiC inclusions can be grown by using nearly on-axis (about 0.3°off-axis) 4H-SiC( 000 1) [128,211]. Although the reasons for this success are unclear at present, the difference in the surface energy was suggested (this is also the reason why bulk 4H-SiC can be easily grown on a ( 000 1) seed by sublimation) [46].…”
Section: Homoepitaxy On Nearly On-axis Growthmentioning
confidence: 90%
“…Homoepitaxy of dislocation-free 4H-and 6H-SiC(0001) by using small (0.4 mm × 0.4 mm) mesa structures is also reported [210]. More recently, it was found that 4H-SiC without 3C-SiC inclusions can be grown by using nearly on-axis (about 0.3°off-axis) 4H-SiC( 000 1) [128,211]. Although the reasons for this success are unclear at present, the difference in the surface energy was suggested (this is also the reason why bulk 4H-SiC can be easily grown on a ( 000 1) seed by sublimation) [46].…”
Section: Homoepitaxy On Nearly On-axis Growthmentioning
confidence: 90%
“…The dependence of k C on crystallographic orientation of the 4H-SiC layer was demonstrated by Kimoto, while Kojima et al [6] reported on the influence of reactor pressure on k C . In the analysis presented below we propose to consider k C as an adjustable parameter, dependent on growth conditions and to keep in mind that k N should remain close to 1.…”
Section: Site Competition Between Nitrogen and Carbonmentioning
confidence: 92%
“…For hexagonal polytypes (4H and 6H-SiC) this problem was (partially) solved basing on the sitecompetition principle, reported by Larkin et al [1]; since the nitrogen incorporates in the sites of carbon sublattice, the decrease of unintentional doping of the layer down to 10 14 cm À3 is possible by raising the supply of carbon-containing species. Since then, numerous studies reported the influence of the chemical vapor deposition (CVD) growth conditions on doping of layers grown on different crystalline faces of 4H-and 6H-SiC [2][3][4][5][6][7]. The experimental results, sometimes contradictory, were obtained on different types of CVD systems (horizontal/vertical/barrel, hot/ cold wall, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, 41 off-cut 4H-SiC substrates have the disadvantage of having a relatively higher probability for nucleation on the terraced regions. Also, at low growth temperatures surface imperfections could easily suppress step-flow growth [14], thereby resulting in TD formation. Therefore, high growth temperatures help to minimize TDs that originate from surface imperfections.…”
Section: Temperaturementioning
confidence: 99%